Numerical prediction of rotary-kiln foundation temperature at an early age - Adek Tasri (Universitas Negeri Padang, 2022)
The hydration heat confined to the core of the mass concrete during the hydration reaction causes a temperature rise and irregular temperature distribution in the concrete. High temperatures in concrete cause Delay Ettringite Formation (DEF) that cause damage several years after pouring, especially if the concrete is in an acidic environment. The uneven temperature distribution causes thermal stresses that can initiate cracks in the concrete surface. This article discusses a prediction of temperature distribution inside a mass concrete used as a rotary kiln foundation. We measure the heat of hydration of the concrete sample using an adiabatic calorie meter and derive the heat of hydration equation from the measurement data. The hydration heat was used in numerical calculations to obtain the temperature distribution, maximal temperature and temperature differential. The numerical calculation shows that the maximum foundation temperature was 64.01 0C. This temperature is still below the limit temperature for the occurrence of Delayed Ettringite Formation (DEF). The core region has the highest temperature, while the surfaces have the lowest temperature. The difference between the highest and lowest temperatures is 37.40 0C. However, the temperature differential exceeds the safe limit, 20 0C, so heat treatment to prevent cracking needs to be done.